2013
DOI: 10.1680/feng.12.00016
|View full text |Cite
|
Sign up to set email alerts
|

Foundations on collapsible soils: a review

Abstract: This paper describes studies done by various researchers on one form of problematic soils that are not suitable to be used as foundation subsoil. Methods to identify these soils are provided, and various methods suggested for the design of proper foundations to combat their detrimental effects. These types of soils are commonly termed ‘collapsible’. Collapsible soils are moisture sensitive in that an increase in moisture content is the primary triggering mechanism for their volume reduction (compression). Thes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
24
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(24 citation statements)
references
References 11 publications
0
24
0
Order By: Relevance
“…These are loessial type soils (Kalantari, 2012) and are generally unsaturated in state as found naturally (Zhu and Chen, 2009). Examples of such soils are wind-blown sand, loess or alluvial deposits generally found in arid or semi-arid environments where the evaporation of soil moisture is so high that they do not have sufficient time to consolidate under their own weight (Pye and Tsoar, 1990).…”
Section: Collapsible Soilsmentioning
confidence: 99%
See 4 more Smart Citations
“…These are loessial type soils (Kalantari, 2012) and are generally unsaturated in state as found naturally (Zhu and Chen, 2009). Examples of such soils are wind-blown sand, loess or alluvial deposits generally found in arid or semi-arid environments where the evaporation of soil moisture is so high that they do not have sufficient time to consolidate under their own weight (Pye and Tsoar, 1990).…”
Section: Collapsible Soilsmentioning
confidence: 99%
“…Efforts have been made by various workers (Holtz and Hilf, 1961;Jennings and Knight, 1975;Jasmer and Ore, 1987;Anderson and Reimer, 1995;Reznik, 2007;Gaaver, 2012;Kalantari, 2012;Rezaei et al, 2012) to characterise collapsible soils based on laboratory testing. As stated earlier, Holtz and Hilf (1961) suggested that loess-like soils that have a void ratio large enough to exceed its moisture content beyond its liquid limit upon saturation are vulnerable to collapse.…”
Section: Collapsible Soilsmentioning
confidence: 99%
See 3 more Smart Citations